5(x+3)+9=3x-6+6

Simple and best practice solution for 5(x+3)+9=3x-6+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+9=3x-6+6 equation:


Simplifying
5(x + 3) + 9 = 3x + -6 + 6

Reorder the terms:
5(3 + x) + 9 = 3x + -6 + 6
(3 * 5 + x * 5) + 9 = 3x + -6 + 6
(15 + 5x) + 9 = 3x + -6 + 6

Reorder the terms:
15 + 9 + 5x = 3x + -6 + 6

Combine like terms: 15 + 9 = 24
24 + 5x = 3x + -6 + 6

Reorder the terms:
24 + 5x = -6 + 6 + 3x

Combine like terms: -6 + 6 = 0
24 + 5x = 0 + 3x
24 + 5x = 3x

Solving
24 + 5x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
24 + 5x + -3x = 3x + -3x

Combine like terms: 5x + -3x = 2x
24 + 2x = 3x + -3x

Combine like terms: 3x + -3x = 0
24 + 2x = 0

Add '-24' to each side of the equation.
24 + -24 + 2x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 2x = 0 + -24
2x = 0 + -24

Combine like terms: 0 + -24 = -24
2x = -24

Divide each side by '2'.
x = -12

Simplifying
x = -12

See similar equations:

| z/5-10=35 | | x+1/x+4=x-5/x+1 | | x-5/2=6 | | 5/x-1=-10/x+5 | | 4x+8/x-2=6 | | 4x-2/2=23 | | 4x-3-5x=8+2x | | 3x+7y=12.5 | | 8x+4/2=30 | | 0.17x-0.4(x+1700)=-2566 | | 2x=5x+3 | | q/3+7=11 | | 12=0.4x+0.04 | | 4s^2+10+18s=0 | | 4s^2=-10-18s | | np-5=-17 | | 2(2w-3)+2w=102 | | 3600=x+x/2 | | (X/7)-2=x/5 | | -6x+2x(5y+9)= | | 3k-5=-14 | | 9x-7=9(x+8) | | 21x-7=19x+1 | | 20*95-2x+89/2 | | 2(x+6)=8x+2-6x+10 | | 5x^2-15=4x^2-2x | | 4b-a(3a+6b)-9= | | 0.6(x+300)=0.67x-338 | | 0.3(3z+6)+6.7=0.7(3z-5) | | 2x+6-30-6x=3x+4 | | (7z-a)(3z+2a)= | | 4-(2x-4)=3(3x-7) |

Equations solver categories